Changes in Sprint Momentum in Elite Rugby Union Players over a Three-Season Period - Federico Nigro; Giovanni Biondi; Pietro Sirocchi; Carlo Cavaletti; Rocco Di Michele (Applied Sciences, 2025)
The purpose of this study was to analyze the trend of sprint momentum over three consecutive seasons in elite rugby union players, to assess how body mass and sprinting speed affected changes in momentum, and to determine the impact of between-season changes in momentum on a selection of technical/tactical match performance indicators. The body mass, 10-m sprinting speed, and momentum of n = 37 elite rugby union players (age: 25.9 ± 2.8 y; height: 186.5 ± 7.3 cm; 22 forwards and 15 backs) were assessed over three consecutive seasons (2018–2021). Linear mixed-effects models were used to examine the impact of between-season changes in body mass and speed on momentum, and of body mass, speed, and momentum on technical indicators. Increased speed and body mass led to higher momentum (ES = 1.06–1.44). Speed changes improved effective carries, ineffective carries, carries, linebreaks, and offloads (ES = 0.48–1.17), while they reduced tackles (ES = −1.29). Changes in body mass reduced tackles (ES = −0.22) and improved effective carries (ES = 0.89) and carries (ES = 0.75). Changes in momentum reduced tackles (ES = −0.26) and ineffective contests (ES = −0.27), and improved offloads (ES = 0.61), effective carries (ES = 0.59), and carries (ES = 0.51). In conclusion, between-season improvements of momentum are achievable in elite rugby players, and, together with changes in speed and/or body mass, can have an impact on the technical/tactical performance during match play.